Students’ Perception of Teachers’ Bilingual Language Use in EFL Classroom - Desi Surayatika (Global Expert: Jurnal Bahasa dan Sastra, 2020)
ABSTRACTStudents’ perception of teachers’ bilingual language use was based on bilingual approach in English language learning in which the students’ first language ( L1 ) is combined with the target language ( L2 ) being studied to be a language instruction used by the teacher to conduct an English classroom.  The purpose of this research was to find out the students’ perception toward the use of Bilingual language they are English and Indonesian by the teacher in EFL classroom. This research was a qualitative approach with the forty students as the sample. In collecting the data, questionnaire was used. The data was analyzed through Likert Scale in order to find out students’ perception of teachers’ bilingual language use in EFL classroom. Based on the result of data analysis and interpretation of the data gained from questionnaire, it indicates that students show their positive perceptions to the use of bilingual language done by the teacher as language instruction in their English classroom. Finally, the result of the research would give a contribution to the improvement of the classroom language instruction used by the teacher in an English language learning classroom particularly for teaching the students who were learning English as a foreign language ( EFL ).Keyword : Bilingual, Students’ Perception, language use, EFL classroomABSTRAKPersepsi siswa tentang penggunaan dua bahasa oleh guru didasarkan pada pendekatan bilingual dalam pembelajaran bahasa Inggris di mana bahasa pertama siswa ( L1 ) dikombinasikan dengan bahasa target (L2) yang dipelajari menjadi pengajaran bahasa yang digunakan oleh guru untuk melaksanakan pembelajaran bahasa Inggris di kelas. Tujuan dari penelitian ini adalah untuk mengetahui persepsi siswa terhadap penggunaan dua bahasa yaitu bahasa Inggris dan bahasa Indonesia oleh guru di kelas EFL. Penelitian ini menggunakan metode kualitatif dengan empat puluh siswa sebagai sampel. Dalam mengumpulkan data, kuesioner digunakan. Data dianalisis melalui Skala Likert untuk mengetahui persepsi siswa tentang penggunaan dua bahasa oleh guru di kelas EFL. Berdasarkan hasil analisis data dan interpretasi data yang diperoleh dari kuesioner, hal ini menunjukkan bahwa siswa memiliki persepsi positif  terhadap penggunaan dua bahasa yang dilakukan oleh guru sebagai bahasa pengantar di kelas bahasa Inggris.. Pada akhirnya, hasil penelitian diharapkan dapat memberikan kontribusi pada peningkatan pengajaran bahasa Inggris di kelas yang digunakan oleh guru di kelas pembelajaran bahasa Inggris terutama untuk mengajar siswa yang belajar bahasa Inggris sebagai bahasa asing ( EFL ).Kata kunci : Dua bahasa, Persepsi Siswa, penggunaan bahasa, kelas EFL